Пошаговое объяснение:
(900-x:6)*5=4200
900-x:6=4200:5
900-x:6=840
x:6 = 900-840
x:6 = 60
x = 60*6
x = 360
(900-360:6)*5=4200
(900-60)*5=4200
840*5=4200
4200=4200
325+(90-n):17=330
(90-n):17=330-325
(90-n):17=5
90-n=5*17
90-n=85
n=90-85
n=5
325+(90-5):17=330
325+85:17=330
325+5=330
330 = 330
Пошаговое объяснение:
(900-x:6)*5=4200
900-x:6=4200:5
900-x:6=840
x:6 = 900-840
x:6 = 60
x = 60*6
x = 360
(900-360:6)*5=4200
(900-60)*5=4200
840*5=4200
4200=4200
325+(90-n):17=330
(90-n):17=330-325
(90-n):17=5
90-n=5*17
90-n=85
n=90-85
n=5
325+(90-5):17=330
325+85:17=330
325+5=330
330 = 330